O gênero na propaganda de moda brasileira analisada a partir dos elementos de design do vestuário - Passarelli, Ana Paula Martins (2018)
This research intends to develop semiotic analysis about the signs of gender in advertising and fashion propaganda. It seeks to understand how fashion propaganda represented gender roles and identities, and how it built and maintained stereotypes for men and women. Fashion is a semiotic system that acts with codes in building meaning towards gender roles. It expresses people's ideas of how men and women should perform. But in a liquid, hypermodern society like Bauman and Lipovetsky define, would it not be limiting to continue categorizing bodies in a binary way? Butler states that the body is socially signified as a passive medium, upon which are inscribed cultural meanings. It can also be signified as the instrument by which the will to appropriation or interpretation determines its cultural meaning. Therefore, the body is constructed from the signs of the cultural identity of gender. During the twentieth century there were cultural cycles that brought new references of identity, especially in pop culture. David Bowie, Prince and also Brazilian artists such as Ney Matogrosso were important figures for pop culture and to raise the discussion about gender identity beyond the binary spectrum. Today, contemporary authors such as Connell and Killermann collaborate on the work of constructing new meanings for gender roles. This research is limited to analyzing Brazilian fashion advertising. Barnard, Bauman, Lipovetsky and Butler, authors like Connell, Foucault, Killerman, Santaella and Polhemus are part of the theoretical framework that seeks to base this study that will have as a methodology of analysis the basis of psychoanalytic semiotics and will use the Lacanian categories: real, symbolic and imaginary. The corpus of this research is composed of images of fashion propaganda and videos published on proprietary brands channels in Brazil between 2014 and 2018. Two images and two videos will be analyzed, which were important and generated big discussions about representations of gender roles. Some elements of fashion design such as: skirt, jeans and high heels will be used at analysis to understand the articulation between fashion, bodies and how propaganda could have intensified the crystallization of gender roles